A recyclable supramolecular nanofiber composite membrane and its preparation method and application
Through the preparation method of supramolecular nanofiber composite membrane with nitrogen-containing heterocyclic compounds and aromatic acid, the hazards of nanofiber membrane preparation equipment and the load stability of nanomaterials are solved, and efficient and environmentally friendly air purification materials are achieved, suitable for large-scale production and Recycling.
Patent Information
- Application Number
- CN202410907011.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-08
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-07-08
AI Technical Summary
The existing nanofiber membrane preparation methods have equipment hazards, high voltage, low efficiency and instability problems, and the stability of nanomaterial loads on the membrane surface is difficult to ensure, which limits its promotion and application in the fields of air purification and other fields.
The preparation method of supramolecular nanofiber composite film combining nitrogen-containing heterocyclic compounds with aromatic acid is adopted. The self-assembly of ultrasonic environment and temperature gradients is formed into a three-dimensional network structure. The nanomaterials are firmly combined as crystal nucleus growth points to improve load stability and Reversible characteristics realize recycling.
It realizes simple process and low-cost nanofiber membrane preparation, improves the load stability of nanomaterials and the air purification efficiency of the membrane, and has the characteristics of recycling, which is suitable for large-scale production and environmental protection applications.
Smart Images

Figure CN118577128B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nanofiber membrane materials, and specifically relates to a preparation method and application of a recyclable supramolecular nanofiber composite membrane. Background Art
[0002] As an important component of nonwoven materials, nanofiber membranes have shown promising application prospects in the fields of air purification, oil-water separation, tissue engineering, and drug release due to their controllable wettability, good porosity, and excellent pore connectivity. Currently, nanofiber membranes are mainly prepared by electrospinning technology and its derivative processes. The essential defects of this method, such as the special equipment required, the dangers caused by high voltage, the low efficiency and instability in the production of high-density nanofibers, have greatly limited their promotion and application in related fields.
[0003] In recent years, soft functional materials based on supramolecular self-assembly have attracted the attention of many scholars due to their unique microstructure and physicochemical properties. Small molecular monomers with special functional groups can spontaneously assemble into supramolecular compounds with three-dimensional network-like nanofiber structures in a hierarchical and orderly manner in corresponding solvents (water, organic solvents, ionic liquids, etc.) through non-covalent interactions (hydrogen bonds, host-guest interactions, van der Waals forces, hydrophobic interactions, π-π stacking, electrostatic interactions, etc.) under certain external stimuli (light, pH value, temperature, ultrasound, etc.). Through this "bottom-up" design strategy, a series of multifunctional supramolecular nanofiber membrane materials can be efficiently customized under mild and environmentally friendly conditions. Non-covalent bonds give these materials intrinsic reversible properties, which enables them to be degraded or recycled after use.
[0004] Nanomaterials can be divided into photocatalytic organic matter removal nanomaterials, porous nanomaterials with adsorption capacity, electret nanomaterials with electrostatic adsorption, etc. In practical applications, nanomaterials are often loaded on the surface of nanofiber membranes with high specific surface area to improve their thermal stability, catalytic activity, practicality, etc. However, how to load various forms of nanomaterials on the surface of nanofiber membranes and the stability of nanomaterials after loading are the difficulties faced in the current research process. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a recyclable supramolecular nanofiber composite membrane with simple process, energy saving and environmental protection, simple required equipment and low preparation cost, so that it can be applied to environmental protection fields such as air purification.
[0006] In order to achieve the above-mentioned purpose, the present invention adopts the following technical solutions:
[0007] A recyclable supramolecular nanofiber composite membrane, which is formed by a three-dimensional network of nitrogen-containing heterocyclic compounds-aromatic acids-nanomaterial supramolecular nanofibers with a diameter of 10-500 nanometers and an aspect ratio of greater than 6000 and less than or equal to 10000. The pore size range of the supramolecular nanofiber composite membrane is 0.01-25 microns, wherein the mass ratio of the nitrogen-containing heterocyclic compounds, aromatic acids and nanomaterials is (45-49.95%): (45-49.95%): (0.1-10%).
[0008] A method for preparing a recyclable supramolecular nanofiber composite membrane comprises the following steps:
[0009] (1) adding a nitrogen-containing heterocyclic compound and an aromatic acid into an organic solvent, stirring to react and precipitating a eutectic, and drying to obtain a composite precursor;
[0010] (2) The composite precursor, nanomaterial and solvent are heated and mixed to obtain a stable suspension, in which the composite precursor can be dissolved in the solvent, but the nanomaterial is not dissolved;
[0011] (3) lowering the temperature of the suspension obtained in step (2) in an ultrasonic environment to obtain a composite supramolecular nanofiber dispersion;
[0012] (4) The composite supramolecular nanofiber dispersion prepared in step (3) is vacuum filtered to obtain a wet film, which is then dried to obtain a supramolecular nanofiber composite membrane.
[0013] Lower the temperature of the suspension, and the composite precursor will spontaneously form supramolecular nanofibers of nitrogen-containing heterocyclic compounds-aromatic acids-nanomaterials with nanomaterials as attachment points under the action of temperature gradient. The nanofibers are interwoven to form a network structure, and then filtered, and small networks are stacked into a large network, thereby forming a supramolecular nanofiber composite membrane. During the crystallization of the composite precursor, the nitrogen-containing heterocyclic compound and the aromatic acid are bonded by hydrogen bonds, and the aromatic acids are stacked with benzene rings to form nanofibers with high aspect ratio. The nanomaterials serve as attachment points for the growth of supramolecular nanofiber nuclei and can be firmly bonded to the nanofibers.
[0014] The mass percentages of the nitrogen-containing heterocyclic compound, aromatic acid and organic solvent in step (1) are (0.1-5%): (0.1-5%): (90-99.8%), respectively, and the reaction temperature is 20-80°C.
[0015] The stirring method in step (1) can be a conventional stirring method known to those skilled in the art, such as magnetic stirring and mechanical stirring. If magnetic stirring is used, the rotation speed is 100~1000r / min and the time is 1~48h. The drying method used in step (1) can be a common drying method known to those skilled in the art, such as vacuum drying and normal pressure drying, which is not limited here, and the purpose is to remove excess solvent. If vacuum drying is used, the vacuum drying temperature is 30~80℃, the vacuum degree is 0.1~20Pa, and the vacuum drying time is 6~50h.
[0016] The nitrogen-containing heterocyclic compound in step (1) is any one of cyanuric fluoride, melamine, cyanuric acid, cyanuric chloride, thiocyanuric acid, trichloromelamine, melamine phosphate, adenine, guanine, cytosine, isoquinoline, pyridine-3-carboxylic acid, thymine, and malonyl urea.
[0017] The aromatic acid in step (1) is an acid containing a benzene ring, such as any one of benzoic acid, terephthalic acid, trimesic acid, phthalic acid, trimesic acid, pyromellitic acid, 5-nitroisophthalic acid, 3,4,5-trihydroxybenzoic acid, p-hydroxycinnamic acid, caffeic acid, probenecid, mefenamic acid, salicylic acid, and benoyl ester.
[0018] The organic solvent in step (1) is any one of methanol, acetone, anhydrous ethanol, dimethyl sulfoxide, N,N-dimethylformamide and carbon tetrachloride.
[0019] The mass percentages of the composite precursor, the nanomaterial, and the solvent in step (2) are (0.01-0.5%): (0.01-0.5%): (99-99.98%), respectively.
[0020] Preferably, the composite precursor solution in step (2) is a hot supersaturated solution, and the temperature is preferably 40-180°C.
[0021] The nanomaterials described in step (2) include nanoparticles, nanorods, nanofibers, and nanofilms in terms of morphology. In terms of function, they include photocatalytic organic matter removal nanomaterials, porous nanomaterials with adsorption capacity, and electret nanomaterials with electrostatic adsorption. Specifically, the nanomaterials include, but are not limited to, any one of nanometal particles, molecular sieves, carbon nanotubes, quantum dots, COFs, MOFs, HOFs, HCPs, g-C3N4, Fe3O4, SiO2, TiO2, Al2O3, AlN, ZnO, SnO2, WO3, Si3N4, ZrO2, CuO, CdS, MXene, graphene oxide / graphene, boron nitride, boehmite, molybdenum disulfide, molybdenum disulfide, nano calcium phosphate, nano hydroxyapatite, nano cellulose, nano perylene imide, and aramid nanofibers. On the one hand, the nanomaterial can be loaded into the nanofiber membrane by the above method; on the other hand, the added nanomaterial acts as a crystal nucleus to drive the formation of three-dimensional network-like supramolecular nanofibers, thereby improving the binding force between the nanomaterial and the nanofiber, improving its loading stability, and at the same time improving the surface roughness and surface area of the membrane material and the nanofiber membrane. In addition, the present invention only mixes the nanomaterial into the solution of the composite precursor, and embeds the nanomaterial into the three-dimensional network structure through subsequent crystallization, without limiting the form and type of the nanomaterial, thereby improving the universality of the nanomaterial.
[0022] The solvent in step (2) includes but is not limited to any one of acetone, deionized water, ethyl acetate, dimethyl sulfoxide, N,N-dimethylformamide, and carbon tetrachloride. The composite precursor can be dissolved in the solvent, while the nanomaterial is not soluble in the solvent, and the specific solvent is selected according to the actual situation.
[0023] In step (3), the suspension obtained in step (2) is placed in an environment of 0-40° C. to crystallize the composite supramolecular nanofibers. During the crystallization process, the suspension is placed in an ultrasonic environment with an ultrasonic frequency of 10-75 kHz, a power of 5-1000 W, and a time of 0.5-12 h. Ultrasound can promote the formation of composite supramolecular nanofiber crystals and obtain a more uniform three-dimensional network structure.
[0024] The drying method used in step (4) can be a common drying method known to those skilled in the art, such as vacuum drying, atmospheric pressure drying, etc., and is not limited here. If vacuum drying is used, the vacuum drying temperature is 20-80°C, the vacuum degree is 0.2-10Pa, and the vacuum drying time is 4-60h.
[0025] The composite membrane of the present invention is applied to the field of air purification, especially PM 2.5 The composite membrane can also be used as a substitute for flexible substrates or traditional nonwoven materials.
[0026] The recyclable supramolecular nanofiber composite membrane recycling method is:
[0027] (1) The filtered supramolecular nanofiber composite membrane is added to the solvent. After heating, the three-dimensional network structure of the supramolecular nanofiber membrane is decomposed into composite precursors and nanomaterials. The composite precursors are dissolved in the solvent again, and the nanomaterials and adsorbed smoke PM 2.5 Insoluble in solvent, filtered while hot to obtain composite precursor solution, as well as nanomaterials and PM 2.5 A solid mixture;
[0028] (2) The solid mixture is added to an organic solvent and centrifuged to obtain nanomaterials, PM 2.5 It can be dissolved in the organic solvent, while the nanomaterial is not soluble;
[0029] (3) The separated nanomaterials are added back into the composite precursor solution and ultrasonically cooled to grow again into supramolecular nanofiber composite membranes.
[0030] The principle of the present invention is: using the co-crystal formed by nitrogen-containing heterocyclic compounds and aromatic acids as composite precursors, and driving their self-assembly into long-range ordered supramolecular nanofibers "from bottom to top" in a thermally induced crystallization manner. Under the action of temperature gradient, the composite precursors are assembled into a three-dimensional network-like nanocrystalline fiber structure through hydrogen bonds and π-π stacking. In essence, the thermodynamic driving force triggers the crystallization, crystallographic mismatch nucleation, fiber growth and branching of nanocrystalline fibers, and these factors dominate the final structure of the supramolecular complex. It is well known that nucleation is the assembly process of atoms or molecules to reach a critical aggregation size by overcoming energy barriers. In the present invention, the supersaturated state of the solution containing the precursor is a thermodynamic prerequisite for the nucleation and growth of the crystalline phase. In the crystallization growth process of new nanocrystalline fibers, heterogeneous nucleation will generally occur on specific substrates, such as small particles, bubbles, nanoparticles or formed nanocrystalline fibers. The presence of these substrates usually shortens the interface free energy, thereby reducing the nucleation barrier. When there is an interface structure mismatch between the substrate and the nucleation phase, the new crystal layer will deviate from the optimal structural matching position. Once mismatched nucleation and growth occur in the crystal, new crystal domains with different orientations will appear on the surface of the mother crystal to form new nanocrystalline fibers. Countless nanocrystalline fibers eventually form a multi-domain network, which determines the microstructure of the supramolecular compound. The present invention realizes the controllable self-assembly of composite supramolecular nanofibers, and its structure can be precisely regulated by the preparation conditions. Through simple filtration and drying, the fully dispersed supramolecular nanofibers can spontaneously form a porous film with good mechanical properties, which can replace traditional nonwoven materials.
[0031] The preparation method of the present invention and the obtained supramolecular nanofiber and composite membrane have the following beneficial effects: (1) the raw materials used are low in cost, easy to obtain and convenient to modify; (2) the preparation process is simple and efficient, and suitable for large-scale production; (3) the supramolecular nanofiber composite membrane has a stable structure and can be stably stored for 6 to 12 months; (4) by adjusting the preparation conditions (precursor ratio, thermal induction temperature, nanomaterials, etc.), supramolecular nanofiber composite membranes with different microstructures and properties can be prepared; (4) the three-dimensional network-like nanofiber structure combined with the loaded functional nanoparticles is beneficial to PM 2.5 Capture and removal of harmful gases; (5) The reversible intrinsic properties of supramolecular materials endow supramolecular nanofiber composite membranes with closed-loop recovery and recycling capabilities, which have considerable application prospects and practical value. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a physical photograph of the supramolecular nanofiber composite membrane prepared in Example 1 of the present invention.
[0033] Figure 2 This is a SEM photograph of the supramolecular nanofiber composite membrane prepared in Example 2 of the present invention.
[0034] Figure 3 This is a SEM photograph of the supramolecular nanofiber composite membrane prepared in Example 3 of the present invention.
[0035] Figure 4 This is a schematic photograph of the dissolution-recrystallization cycle of the composite supramolecular nanofibers prepared in Example 4 of the present invention.
[0036] Figure 5 This is a SEM photograph of the supramolecular membrane prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0037] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto. Example 1
[0038] (1) 1.6 g of melamine phosphate and 1.5 g of phthalic acid were placed in 100 g of acetone, and magnetically stirred at 30 ° C at a speed of 100 r / min for 36 h to obtain a eutectic, which was placed in a vacuum drying oven at 35 ° C for 40 h with a vacuum degree of 6.2 Pa to obtain a composite precursor;
[0039] (2) 0.3 g of the composite precursor and 0.15 g of MXene were placed in 100 g of dimethyl sulfoxide and magnetically stirred at 400 r / min at 100 °C for 18 h to obtain a uniform and stable suspension;
[0040] (3) After vacuum degassing, the suspension was placed at 5°C and ultrasonically treated for 0.5 h (10 kHz, 600 W) to obtain a composite supramolecular nanofiber dispersion;
[0041] (4) The nanofiber dispersion was vacuum filtered to obtain a wet film, which was placed in a vacuum drying oven at 80°C for 40 h with a vacuum degree of 2.3 Pa to obtain a supramolecular nanofiber composite membrane.
[0042] Example 2
[0043] (1) 1 g of cyanuric acid and 3.27 g of 5-nitroisophthalic acid were placed in 85 g of carbon tetrachloride, and magnetically stirred at 70 ° C at a speed of 500 r / min for 10 h to obtain a eutectic, which was placed in a vacuum drying oven at 40 ° C for 20 h with a vacuum degree of 0.3 Pa to obtain a composite precursor;
[0044] (2) 0.1 g of the composite precursor and 0.05 g of COF were placed in 125 g of N,N-dimethylformamide and magnetically stirred at 140 °C and 1500 r / min for 3.5 h to obtain a uniform and stable suspension;
[0045] (3) After vacuum degassing the suspension, ultrasonic treatment was performed at 30°C for 0.5 h (25 kHz, 300 W) to obtain a composite supramolecular nanofiber dispersion;
[0046] (4) The nanofiber dispersion was vacuum filtered to obtain a wet film, which was placed in a vacuum drying oven at 40°C for 10 h with a vacuum degree of 3.5 Pa to obtain a supramolecular nanofiber composite membrane.
[0047] from Figure 2 It can be seen that the supramolecular nanofiber composite membrane is composed of a three-dimensional network of nitrogen-containing heterocyclic compounds-aromatic acids-nanomaterial supramolecular nanofibers with a diameter of 200-450 nanometers and an aspect ratio of 7500~9000. The pore size range of the supramolecular nanofiber composite membrane is 1~5 microns.
[0048] Example 3
[0049] (1) 0.2 g of trithiocyanate and 0.14 g of pyromellitic acid were placed in 25 g of dimethyl sulfoxide, and magnetically stirred at 800 r / min for 4 h at 55 ° C to obtain a eutectic, which was placed in a vacuum drying oven at 80 ° C for 6 h with a vacuum degree of 10.2 Pa to obtain a composite precursor;
[0050] (2) 0.8 g of the composite precursor and 0.03 g of graphene were placed in 200 g of ethyl acetate and magnetically stirred at 750 r / min for 11 h at 70 °C to obtain a uniform and stable suspension;
[0051] (3) After vacuum degassing, the suspension was ultrasonically treated at 10°C for 3 h (50 kHz, 800 W) to obtain a composite supramolecular nanofiber dispersion;
[0052] (4) The nanofiber dispersion was vacuum filtered to obtain a wet film, which was placed in a vacuum drying oven at 25°C for 5 h with a vacuum degree of 0.5 Pa to obtain a supramolecular nanofiber composite membrane.
[0053] from Figure 3 It can be seen that the supramolecular nanofiber composite membrane is composed of a three-dimensional network of nitrogen-containing heterocyclic compounds-aromatic acids-nanomaterial supramolecular nanofibers with a diameter of 50-500 nanometers and an aspect ratio of 6000~8000. The pore size range of the supramolecular nanofiber composite membrane is 0.05~15 microns.
[0054] Example 4
[0055] (1) 0.4 g of melamine and 0.67 g of trimesic acid were placed in 40 g of anhydrous ethanol, and magnetically stirred at 200 r / min at 40 ° C for 1.5 h to obtain a eutectic, which was placed in a vacuum drying oven at 60 ° C for 12 h with a vacuum degree of 5.5 Pa to obtain a composite precursor;
[0056] (2) 0.05 g of the composite precursor and 0.015 g of SiO2 were placed in 150 g of deionized water and magnetically stirred at 90 °C and 1000 r / min for 6 h to obtain a uniform and stable suspension;
[0057] (3) After vacuum degassing, the suspension was placed in a constant temperature box at 20°C for 2 hours to obtain a composite supramolecular nanofiber dispersion;
[0058] (4) The nanofiber dispersion was vacuum filtered to obtain a wet film, which was placed in a vacuum drying oven at 60°C for 24 h with a vacuum degree of 10.1 Pa to obtain a supramolecular nanofiber composite membrane.
[0059] Example 5
[0060] (1) 0.8 g of tri-filtered melamine and 0.87 g of terephthalic acid were placed in 80 g of N,N-dimethylformamide, and magnetically stirred at 55 °C at a speed of 700 r / min for 20 h to obtain a eutectic, which was placed in a vacuum drying oven at 80 °C for 40 h with a vacuum degree of 17.5 Pa to obtain a composite precursor;
[0061] (2) 1.2 g of the composite precursor and 0.15 g of TiO2 were placed in 250 g of dimethyl sulfoxide and magnetically stirred at 1700 r / min at 40 °C for 2 h to obtain a uniform and stable suspension;
[0062] (3) After vacuum degassing the suspension, ultrasonic treatment was performed at 2.5°C for 8 h (15 kHz, 400 W) to obtain a composite supramolecular nanofiber dispersion;
[0063] (4) The nanofiber dispersion was vacuum filtered to obtain a wet film, which was placed in a vacuum drying oven at 55°C for 8 h with a vacuum degree of 7.1 Pa to obtain a supramolecular nanofiber composite membrane.
[0064] Comparative Example 1
[0065] (1) 1 g of cyanuric acid and 3.27 g of 5-nitroisophthalic acid were placed in 85 g of carbon tetrachloride, and magnetically stirred at 70 ° C at a speed of 500 r / min for 10 h to obtain a eutectic, which was placed in a vacuum drying oven at 40 ° C for 20 h with a vacuum degree of 0.3 Pa to obtain a composite precursor;
[0066] (2) 0.1 g of the composite precursor was placed in 125 g of N,N-dimethylformamide and magnetically stirred at 140 °C and 1500 r / min for 3.5 h to obtain a uniform and stable suspension;
[0067] (3) After vacuum degassing the suspension, ultrasonic treatment was performed at 30°C for 0.5 h (25 kHz, 300 W) to obtain a composite supramolecular nanofiber dispersion;
[0068] (4) The nanofiber dispersion was vacuum filtered to obtain a wet film, which was placed in a vacuum drying oven at 40°C for 10 h with a vacuum degree of 3.5 Pa to obtain a supramolecular nanofiber membrane.
[0069] from Figure 5 It can be seen that the supramolecular nanofiber composite membrane is formed by a three-dimensional network of nitrogen-containing heterocyclic compounds-aromatic acid supramolecular nanofibers with a diameter of 300-500 nanometers and an aspect ratio of 5000-6000, and the pore size range of the supramolecular nanofiber composite membrane is 0.5-10 microns. Analysis of Example 2 and Comparative Example 1 shows that the addition of nanomaterials causes wrinkles and protrusions on the relatively smooth fiber surface, and the higher aspect ratio of the fiber can form more bending space, which is conducive to improving the air purification efficiency.
[0070] The composite membranes prepared in Examples 1-5 and Comparative Example 1 were 3 / h operating flow rate, the concentration is 1.0mg / m 3 The removal rate of sodium chloride aerosol particles with a particle size distribution of 0.225 to 12.5 μm is 800 μg•m −3 PM 2.5 The removal rates of , and formaldehyde are shown in the following table respectively.
[0071]
[0072] It can be seen from the table that the three-dimensional network structure formed by nitrogen heterocyclic compounds and aromatic acids can 2.5 A very good removal effect is achieved, but the removal effect on sodium chloride aerosol and formaldehyde is poor. After loading a small amount of nanomaterials, the removal effects on aerosol, formaldehyde and smoke are greatly improved, showing a strong synergistic effect between the two.
[0073] The filtered supramolecular nanofiber composite membrane is added to the solvent, and the three-dimensional network structure of the supramolecular nanofiber membrane is destroyed by heating, and decomposed into composite precursors and nanomaterials. The composite precursors are dissolved in the solvent again, and the nanomaterials and the adsorbed smoke PM 2.5 Insoluble in solvent, the solution is filtered while hot to obtain a composite precursor solution, as well as nanomaterials and PM 2.5 The solid mixture is treated with an organic solvent such as acetone (PM 2.5 The separated nanomaterials are added to the composite precursor solution again, cooled and grown again into supramolecular nanofiber composite membranes, thus realizing the regeneration and recycling of the composite membranes. Figure 4 This is a schematic photograph of the dissolution-recrystallization cycle of the composite supramolecular nanofibers prepared in Example 4 after use.
[0074] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a recyclable supramolecular nanofiber composite membrane, characterized in that: The following steps are involved: (1) adding a nitrogen-containing heterocyclic compound and an aromatic acid into an organic solvent, stirring to react to precipitate a eutectic, and drying to obtain a composite precursor; (2) heating and mixing the composite precursor, nanomaterial and solvent to obtain a stable suspension, in which the composite precursor can be dissolved in the solvent, but the nanomaterial is not dissolved; (3) lowering the temperature of the suspension obtained in step (2) in an ultrasonic environment to obtain a composite supramolecular nanofiber dispersion; (4) vacuum filtering the composite supramolecular nanofiber dispersion prepared in step (3) to obtain a wet film, and drying to obtain a supramolecular nanofiber composite membrane.
2. The method for preparing a recyclable supramolecular nanofiber composite membrane according to claim 1, characterized in that: The mass percentages of the nitrogen-containing heterocyclic compound, aromatic acid and organic solvent in step (1) are (0.1-5%):(0.1-5%):(90-99.8%) respectively.
3. The method for preparing a recyclable supramolecular nanofiber composite membrane according to claim 1, characterized in that: The nitrogen-containing heterocyclic compound in step (1) is any one of cyanuric fluoride, melamine, cyanuric acid, cyanuric chloride, thiocyanuric acid, trichloromelamine, melamine phosphate, adenine, guanine, cytosine, isoquinoline, pyridine-3-carboxylic acid, thymine, and malonyl urea; the aromatic acid is an acid containing a benzene ring, and the acid containing a benzene ring is selected from any one of benzoic acid, terephthalic acid, trimesic acid, phthalic acid, trimesic acid, pyromellitic acid, 5-nitroisophthalic acid, 3,4,5-trihydroxybenzoic acid, p-hydroxycinnamic acid, caffeic acid, probenecid, mefenamic acid, and salicylic acid; and the organic solvent is any one of methanol, acetone, anhydrous ethanol, dimethyl sulfoxide, N,N-dimethylformamide, and carbon tetrachloride.
4. The method for preparing a recyclable supramolecular nanofiber composite membrane according to claim 1, characterized in that: The mass percentages of the composite precursor, nanomaterial and solvent in step (2) are (0.01-0.5%):(0.01-0.5%):(99-99.98%) respectively.
5. The method for preparing a recyclable supramolecular nanofiber composite membrane according to claim 1, characterized in that: The nanomaterial described in step (2) is any one of nano metal particles, molecular sieves, carbon nanotubes, quantum dots, COFs, MOFs, HOFs, HCPs, g-C3N4, Fe3O4, SiO2, TiO2, Al2O3, AlN, ZnO, SnO2, WO3, Si3N4, ZrO2, CuO, CdS, MXene, graphene oxide, graphene, boron nitride, boehmite, molybdenum disulfide, nano calcium phosphate, nano hydroxyapatite, nano cellulose, nano perylene imide, and aramid nanofibers.
6. The method for preparing a recyclable supramolecular nanofiber composite membrane according to claim 1, characterized in that: The solvent in step (2) includes any one of acetone, deionized water, ethyl acetate, dimethyl sulfoxide, N,N-dimethylformamide, and carbon tetrachloride.
7. The method for preparing a recyclable supramolecular nanofiber composite membrane according to claim 1, characterized in that: In step (3), the suspension obtained in step (2) is placed in an environment of 0 to 40° C. to crystallize the composite supramolecular nanofibers. During the crystallization process, the suspension is placed in an ultrasonic environment with an ultrasonic frequency of 10 to 75 kHz, a power of 5 to 1000 W, and a time of 0.5 to 12 h. Ultrasound can promote the formation of composite supramolecular nanofiber crystals and obtain a more uniform three-dimensional network structure.
8. A composite membrane prepared according to the preparation method according to any one of claims 1 to 7.
9. Use of the composite membrane according to claim 8 as a filter material, and as a flexible substrate or nonwoven material.
10. The method for recycling composite membrane according to claim 8, characterized in that: (1) The filtered supramolecular nanofiber composite membrane is added to a solvent. After heating, the three-dimensional network structure of the supramolecular nanofiber composite membrane is decomposed into a composite precursor and a nanomaterial. The composite precursor is dissolved in the solvent again, and the nanomaterial and the adsorbed smoke PM 2.5 Insoluble in solvent, filtered while hot to obtain composite precursor solution, as well as nanomaterials and PM 2.5 A solid mixture; (2) The solid mixture is added to an organic solvent and centrifuged to obtain nanomaterials, PM 2.5 It can be dissolved in the organic solvent, while the nanomaterial is not soluble; (3) The separated nanomaterials are added back into the composite precursor solution and ultrasonically cooled to grow again into supramolecular nanofiber composite membranes.
